Short communicationsCircumflex-to-bronchial artery fistula with saccular aneurysm - Eryilmaz, Ufuk; Gungor, Hasan; Uyar, Samet; Akgullu, Cagdas; Selvi, Mithat; Onay, Sevil; Ozkisacik, Erdem (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We report a case of fistulous communication with two saccular aneurysms (9 mm and 7 mm) between the sinoatrial branch of the circumflex artery and the bronchial arteries.